Finishing properties of bleached and unbleached bio-polyurethane wood coating - James, Redzuan Mohammad Suffian; Md Tahir, Paridah; Mohd Yusof, Norwahyuni; Osman al-Edrus, Syeed Saifulazry; Zainal Abidin, Zurina; Uyup, Mohd Khairun Anwar; Antov, Petar; Fatriasari, Widya; Lee, Seng Hua (College of Natural Resources, 2024)
To obtain a more appealing wood coating with lighter color, bleaching treatment was employed. Bleached and unbleached bio-polyurethane (PU) coating was prepared using liquefied bamboo and was applied to rubberwood. The coated wood surface was examined for adhesion, scratch, abrasion, impact, and resistance to common household chemicals. The results revealed that the bleaching of liquefied bamboo exerted mixed effects on the finishing properties of the bio-PU coating. Specifically, the surface coated with unbleached bio-PU coating exhibited noticeably higher levels of scratch and impact resistance compared to the surface coated with bleached bio-PU coating. However, both the adhesion and abrasion properties were found to be similar in both cases. Both bleached and unbleached bio-PU coating exhibited similar resistance to various household chemicals, with exception of acetic acid. This research demonstrated a method for producing semi-transparent bio-PU from bamboo biomass for use in wood coating. Bleaching treatment is feasible to produce light-colored coating without significantly affecting the finishing properties of the bio-PU coating.